Pressure effects on electronic structure and magnetic properties of the FeSe(Te) superconductors - Grechnev, G.E.; Panfilov, A.S.; Desnenko, V.A.; Fedorchenko, A.V.; Zhuravleva, I.P.; Gnatchenko, S.L.; Tsurkan, V.; Chareev, D.A.; Kozlyakova, E.S.; Volkova, O.S.; Vasiliev, A.N. (Физика и техника высоких давлений, 2012)
The magnetic susceptibility χ of the FeSe and FeTe compounds, which form the simplest FeSe(Te) system of the novel iron-based superconductors, is studied in the normal state under hydrostatic pressure. A substantial positive pressure effect on χ is detected at low temperatures for both compounds. At room temperature, this effect is found to be also strong, but it is negative for FeSe and positive for FeTe. Ab initio calculations of the pressure dependent electronic structure and magnetic susceptibility indicate that FeSe and FeTe are close to magnetic instability with dominating enhanced spin paramagnetism. The calculated paramagnetic susceptibility exhibits a strong dependence on the unit cell volume and the height Z of chalcogen species from the Fe plane. The observed large positive pressure effects on χ in FeTe and FeSe at low temperatures are related to considerable sensitivity of the paramagnetism to the internal parameter Z. It is shown that available experimental data on the strong and nonmonotonic pressure dependence of the superconducting transition temperature in FeSe correlate qualitatively with the calculated behavior of the density of electronic states at the Fermi level.